2011
DOI: 10.1111/j.1365-313x.2011.04638.x
|View full text |Cite
|
Sign up to set email alerts
|

An atypical heterotrimeric G‐protein γ‐subunit is involved in guard cell K+‐channel regulation and morphological development in Arabidopsis thaliana

Abstract: SUMMARYCurrently, there are strong inconsistencies in our knowledge of plant heterotrimeric G-proteins that suggest the existence of additional members of the family. We have identified a new Arabidopsis G-protein c-subunit (AGG3) that modulates morphological development and ABA-regulation of stomatal aperture. AGG3 strongly interacts with the Arabidopsis G-protein b-subunit in vivo and in vitro. Most importantly, AGG3-deficient mutants account for all but one of the 'orphan' phenotypes previously unexplained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
295
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 194 publications
(316 citation statements)
references
References 73 publications
16
295
2
3
Order By: Relevance
“…it is known that the AGB1/AGG3 dimer is an important modulator of reproductive organ shapes (Chakravorty et al, 2011;Li et al, 2012). We found that W109A and S129R fully rescued this reproductive phenotype, whereas the other two tested AGB1 mutants failed to restore the wild-type morphology (Fig.…”
Section: Dissection Of Agb1-2 Signaling In Developmentmentioning
confidence: 58%
“…it is known that the AGB1/AGG3 dimer is an important modulator of reproductive organ shapes (Chakravorty et al, 2011;Li et al, 2012). We found that W109A and S129R fully rescued this reproductive phenotype, whereas the other two tested AGB1 mutants failed to restore the wild-type morphology (Fig.…”
Section: Dissection Of Agb1-2 Signaling In Developmentmentioning
confidence: 58%
“…Plants also possess relatively fewer G-protein subunits when compared with the mammalian systems (Chen et al, 2003;Perfus-Barbeoch et al, 2004;Chakravorty et al, 2011). The most elaborate plant G-protein network identified to date is present in soybean where recent genome duplication has led to existence of 4 Ga, 4 Gb, 12 Gg, and 2 RGS proteins Choudhury et al, 2011Choudhury et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…C. braunii G-protein genes showed an overall nucleotide sequence similarity of 53.1%, 48.1%, and 44.2%/39.2% with Arabidopsis GPA1, AGB1, and AGG1/AGG2, respectively. No sequence homologs were identified for AtAGG3 genes in Chara species, which is not surprising, as sequence homologs of AtAGG3 are present only in higher plants (Chakravorty et al, 2011;Li et al, 2012;Trusov et al, 2012). Conceptually translated amino acid sequences of C. braunii Ga, Gb, and Gg homologs (named CbGa, CbGb, and CbGg, hereafter) exhibit 47.9%, 43.9%, and 18.8%/23.1% identity (66.1%, 58.4%, and 28.6%/41% similarity) with the corresponding Arabidopsis proteins.…”
Section: Resultsmentioning
confidence: 87%